Pelatihan Peningkatan Efisiensi Produksi dan Omset Penjualan UMKM melalui Pemanfaatan Teknologi Informasi dan Lean Manufacturing - Sanusi, Sanusi; Larisang, Larisang; Prakasa Hasibuan, Rizki; Ismail, Ismail; Badruszaman, Anwar (ASOSIASI IDEBAHASA KEPRI, 2024)
The community service activities aim to enhance the capacity of UMKM (Micro, Small, and Medium Enterprises) in RT01 RW13 Batu Besar Batam- Kepri, by leveraging information technology to support economic and business activities. This program includes a series of training sessions focused on the use of information technology, social media, e-commerce platforms, and an understanding of lean manufacturing principles. The methods used involve initial socialization to identify the needs and potential of SMEs, group-based training, and simulations. As a result of this activity, SMEs can improve their production processes, inventory management, and product marketing more effectively. Lean manufacturing principles help SMEs to identify and reduce waste in the production process, thereby improving productivity and product quality. Additionally, there is increased participation in the digital economy, such as selling local products through e-commerce platforms. The program also positively impacts the education sector. Overall, these dedication activities have improved digital literacy and empowered the public, especially SMEs actors, to face the challenges of the digital age.